A Review of Climate Change Finance Policy in Indonesia - Rafii Diaz Rasendriya (Universitas Muhammadiyah Surakarta, 2024)
Climate change has caused negative impacts in various sectors, including the environment, health, and the economy. The government is trying to deal with these impacts with mitigation and adaptation efforts, such as reducing greenhouse gas emissions in a sustainable manner. However, to achieve the emission reduction target in accordance with the NDC, the Government of Indonesia needs a large source of funding. Although the budget from the state budget is still insufficient, the government needs to find additional funding sources, such as loans, grants, cooperation with business entities, donations from international organizations, issuing green bonds, and involving the private sector through CSR. In addition, the government will implement the Value of Carbon Economy (NEK) such as carbon trading, carbon levy, RBP, and other mechanisms, which are expected to support climate change mitigation and adaptation efforts. All of these are expected to help the government achieve the GHG emission reduction target in accordance with the NDC document.